Chinese politics : the Xi Jinping difference - Rosen, Stanley, 1942-; Lynch, Daniel C. (Daniel Christopher) (Abingdon, Oxon ; New York, NY : Routledge, 2024)
Written by a team of leading China specialists, this updated 2nd edition of Chinese Politics explores the dynamics of state power and politics in contemporary China, focusing on the Xi Jinping era. Through its multi-disciplinary contributions, this book explores the extent to which Xi has reshaped the political, economic, socio-cultural, and demographic terrains of the PRC, as well as Beijing's foreign policy. The book will help readers to think productively about the trajectory of these aspects of Chinese politics and society through Xi's current term and beyond. The book also highlights the potential role outside countries and non-state actors might play in shaping China's trajectory as the PRC's economic rise may be stalling. Through each exploration of these issues, the book addresses the central question of what The Xi Jinping Difference has been, and will likely continue to be, in Chinese politics. Key subjects covered in this new edition include: Law and the political system Socialization of youth The fate of the private sector Technology and digital authoritarianism The Belt and Road Initiative Population aging Chinese Politics continues to be an essential textbook for all students of contemporary China as well as scholars interested in the dynamics of political and social change.
Law and the Political System in Xi Jinping's China : The Decline of the Party/State Distinction / Donald Clarke -- Educating the Next Generation : Propping Up the Party and Undermining Alternatives / Karrie J. Koesel -- The Private Economy Under Party-State Capitalism / Margaret M. Pearson, Meg Rithmire, and Kellee S. Tsai -- Xi Jinping's Partnership with Technology Companies and Social Media Platforms / Daniella Stockmann and Ting Luo -- Technology Policy Under Xi Jinping, 2012-2022 / Douglas B. Fuller and Ricardo L. Kotz -- Chinese Urban Poverty : Negligence or Disdain? / Dorothy J. Solinger -- How To Think Xi Jinping Thought / J. Christopher Mittelstaedt and Patricia M. Thornton -- The 20th Party Congress : Toward Personalistic Autarky? / Joseph Fewsmith -- The Evolving Leadership in Xi Jinping's PLA : Factionalism, Weak Coalition, or Military Preparedness? / Victor Shih -- BRI Under Xi Jinping : Fragmented Authoritarianism Beyond the Water's Edge / Andrew Mertha -- Chinese Foreign Policy Under Xi Jinping / June Teufel Dreyer -- Who Is Blamed for the Pandemic? Survey Findings and Implications for the China Model / Yuen Yuen Ang, Twila Tardif, and Wenjia Song -- Implications of the Reformation of China's Demographic Structure / Wang Feng.
"First edition published by Routledge 2010."
"Written by a team of leading China specialists, this updated 2nd edition of Chinese Politics explores the dynamics of state power and politics in contemporary China, focusing on the Xi Jinping era. Through its multi-disciplinary contributions, this book explores the extent to which Xi has reshaped the political, economic, socio-cultural, and demographic terrains of the PRC, as well as Beijing's foreign policy. The book will help readers to think productively about the trajectory of these aspects of Chinese politics and society through Xi's current term and beyond. The book also highlights the potential role outside countries and non-state actors might play in shaping China's trajectory as the PRC's economic rise may be stalling. Through each exploration of these issues, the book addresses the central question of what The Xi Jinping Difference has been, and will likely continue to be, in Chinese politics. Key subjects covered in this new edition include: - Law and the political system - Socialization of youth - The fate of the private sector - Technology and digital authoritarianism - The Belt and Road Initiative - Population aging Chinese Politics continues to be an essential textbook for all students of contemporary China as well as scholars interested in the dynamics of political and social change"-- Provided by publisher.
OCLC-licensed vendor bibliographic record.
Keywords: Xi, Jinping; POLITICAL SCIENCE / General; China -- Politics and government -- 2002-; China -- Economic conditions -- 2000-; China -- Social conditions -- 2000-